2022
DOI: 10.1111/ipd.13039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the characteristics of root canal calcification after regenerative endodontic procedures: A retrospective cohort study over 3 years

Abstract: Aim This study aimed to evaluate the characteristics of root canal calcification after regenerative endodontic procedures (REPs) during long‐term follow‐up. Design Data of children who underwent REPs and were followed up for >3 years in the Department of Pediatric Dentistry, Peking University School and Hospital of Stomatology, Beijing, China, from January 2013 to January 2019, were collected. All the patients were treated by the protocol of REPs based on the American Association of Endodontists (AAE) protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…In Group II, calcification was initially detected in two cases (8.3%) at 6 months and in 2 (9.5%) cases at 12 months. In contrast to the retrospective cohort study,[ 36 ] root canal calcification was found in 78% of cases; this difference may be attributed to the use of calcium hydroxide as intracanal medication and the longer follow-up period (3 years). The underlying cause of calcification in root canals has been attributed to the migration of periodontal stem cells and bone marrow stem cells from the alveolar bone into the bloodstream through the apical foramen.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…In Group II, calcification was initially detected in two cases (8.3%) at 6 months and in 2 (9.5%) cases at 12 months. In contrast to the retrospective cohort study,[ 36 ] root canal calcification was found in 78% of cases; this difference may be attributed to the use of calcium hydroxide as intracanal medication and the longer follow-up period (3 years). The underlying cause of calcification in root canals has been attributed to the migration of periodontal stem cells and bone marrow stem cells from the alveolar bone into the bloodstream through the apical foramen.…”
Section: Discussioncontrasting
confidence: 67%
“…[ 35 ] The apical foramen width of this study exhibited similarities to those reported by Aly et al .,[ 13 ] they observed a reduction of 46.15% in the apical diameter using MTA after 1 year of follow-up. Furthermore, a previous study[ 36 ] reported that 47% of the total teeth achieved complete apical closure at 6 months, and most teeth (96%) achieved apical foramen closure within 24 months. The variation in apical foramen width outcomes in the present study compared to Jiang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation